2020
DOI: 10.1002/apj.2455
|View full text |Cite
|
Sign up to set email alerts
|

Gas–liquid two‐phase flow characteristics of the jet vortex drainage gas production tool based on computational fluid dynamics

Abstract: This study is aimed at the problems of traditional vortex tools in gas wells, including notable pressure losses and short effective distances. An organic combination of jet vortex drainage and gas production tools was designed and installed without additional power equipment. Based on the liquid film force balance model, gas–liquid two‐phase flow and turbulence models of the jet vortex tool were established with UG and Fluent flow simulation software. The gas–liquid mixture was analyzed before and after the je… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The continuous jet model from Liang et al 14 is cited for comparison to show that the self‐excited oscillating pulse jet used in this paper not only has a stronger velocity boosting effect but is also more advantageous in breaking up droplet particles for airflow carrying. As shown in Figures 3, 4 and 5, at an inlet velocity of 5 m/s and a droplet size of 0.01 mm, the axial velocity at the outlet of the pulsed jet model is more than double that of the continuous jet model, resulting in a significant speed increase.…”
Section: Derivation Of Self‐excited Oscillating Cyclone Extraction Toolmentioning
confidence: 99%
See 3 more Smart Citations
“…The continuous jet model from Liang et al 14 is cited for comparison to show that the self‐excited oscillating pulse jet used in this paper not only has a stronger velocity boosting effect but is also more advantageous in breaking up droplet particles for airflow carrying. As shown in Figures 3, 4 and 5, at an inlet velocity of 5 m/s and a droplet size of 0.01 mm, the axial velocity at the outlet of the pulsed jet model is more than double that of the continuous jet model, resulting in a significant speed increase.…”
Section: Derivation Of Self‐excited Oscillating Cyclone Extraction Toolmentioning
confidence: 99%
“…In this paper, we focus on the speed boosting effect. In order to verify the reliability of the numerical simulation results, the experimental procedure designed by Liang et al 14 was used as an indicator for the two cyclonic tools, and the setup is shown in Figure 14.…”
Section: Experimental Verificationmentioning
confidence: 99%
See 2 more Smart Citations
“…New eddy current tools that are different from traditional structures have also been designed [19]. Liang et al [20], for large pressure loss and short effective distance of traditional vortex tools in gas wells, designed and installed the organic combination of jet vortex drainage and gas production tools. The gas-liquid mixture before and after the jet vortex tool was analyzed, and the flow trajectory, the pressure loss, and the liquid volume fraction change were investigated.…”
Section: Introductionmentioning
confidence: 99%